(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
Results on the applicability of microwave assisted synthesized poly(diallyldimethyl ammonium chloride) (polyDADMAC) in reactive dye containing textile wastewater treatment are reported. Diallyldimethylammonium chloride and poly(diallyldimethylammonium chloride) have been characterized by spectral means. The microwave assisted synthesized polyDADMAC has shown some effectiveness in textile wastewater treatment. COD removal efficiency of actual textile wastewater is below 30% whereas the standard dye sample shows about 50-60% COD removal efficiency. TDS and TSS also decreased after treatment of the wastewater with polyDADMAC. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 165-174, 2017